Les commerçants étrangers d’origine africaine dans les quartiers de Maputo (Mozambique) : quels droits à la ville ? - Catherine Fournet-Guérin (Cybergeo, 2018)
In Maputo, the politic and economic capital of Mozambique, a small number of foreigners have been settling since the 2000s. Although they are not numerous, they are very visible in the urban space because of their main activity in retail shops, selling food or other goods. These shops are in the formal sector and the main pattern is a container converted in a local grocer’s shop which can be observed in every area of the city. They are run by African shop-owners coming either from the Great Lakes area, mainly as refugees, or from Western Africa. The paper focuses on their origins, their motivations for choosing Maputo, their life projects, and the reciprocal representations between city dwellers of Maputo and African shop-owners. The key question is how to deal with the dimension of rights to the city, in the extent that locals give right to recognition to foreigners as full inhabitants. The methodology is based on an ethnographic approach focused on everyday life of the African shop-owners and on the cross relations between them and the city dwellers.